(untitled) (The International Journal for Scientific Research, 2024)
In this paper we use families of disjoint sets colouring technique, to introduce some results of edge colouring for minimum and maximum number of colour classes, and introduce a results explains how to find different values of minimum colour classes, and how to maximize minimum number of colour classes for edge colouring, when maximum degree of vertex is fixed, here we prove a result as a method for finding minimum number of colour classes for edge colouring. Families of disjoint sets colouring technique, as generalization technique deal even with graph of multiple edges, and here graph of multiple edges given as application of some examples and results.